MARKET REACTION TO THE ENACTMENT OF FINANCE MINISTER REGULATION NUMBER 120 OF 2023 ON PROPERTY AND REAL ESTATE STOCKS - I Gede Candra Ari Astawa; I Gusti Ngurah Agung Suaryana (Transpublika Publisher, 2024)
The introduction of PMK 120 of 2023, which offers DTP VAT incentives for the construction of landed houses and flats in the 2023 fiscal year, has led to a reaction in the capital market measured by Abnormal Return and Trading Volume Activity. A quantitative Event Study research is conducted to determine if there are any significant differences in Abnormal Return and Trading Volume Activity before and after the implementation of PMK 120 of 2023. Companies in the property and real estate sector listed on the Indonesia stock exchange were selected as the research sample through a purposive sampling method, totaling 84 samples. The One-Sample Wilcoxon Signed Rank Test was used as the analytical tool for this study. The findings of the research indicate that while there were no significant Abnormal Returns, there was a significant increase in Trading Volume Activity, suggesting that PMK 120 of 2023 has altered the expectations of individual investors. It is hoped that investors will be able to make informed decisions to either generate income or mitigate risks in the future capital market environment.